THERAPEUTIC POTENTIAL OF ETHANOL EXTRACT OF ACACIA NILOTICA (L.) DELILE AND ANOGEISSUS LEIOCARPUS (DC.) GUILL. & PERR IN DIABETIC WOUND HEALING: EVIDENCE FROM MALE WISTER RAT (FUDMA JOURNAL OF SCIENCES, 2024)
The use of plants in traditional medicinal systems has been practiced for thousands of years and continues to supply people with new remedies. The current study evaluated the wound healing effect of ethanol extracts of Acacia nilotica pod and Anogeissus leiocarpus stem bark on rat models. Fourty two (42) Streptozotocin (60 mg/kg) induced diabetic male Wistar rats were divided into seven (7) groups of six (6) rats each. A one-centimeter-diameter excision wound was created on the mid-dorsal area of the experimental diabetic rats. The treatment groups were treated daily with the plant extracts by oral administration at doses of 200 mg/kg and 400 mg/kg for 14 days. Blood glucose level, percentage of wound contraction of the experimental rat groups were observed for 21 days. Histopathological examination was also carried out at the end of the experiment. The findings indicated that both A. leiocarpus at doses of 200 mg/kg, 400 mg/kg and A. nilotica at 200 mg/kg enhanced wound contraction in the diabetic rats at day 14 compared to the standard drug (Metformin) which occurred at day 21. This showed a significant reduction in blood glucose level of the treated diabetic rats as well as wound healing effect by the tested plants extract.
Keywords: Acacia nilotica; Anogeissus leiocarpus; Anti-diabetic; Diabetic rat; Streptozotocin; Wound healing